Upaya Peningkatan Pembelajaran Passing Bawah Bolavoli Menggunakan Metode Kooperatif Tipe Teams Games Tournament Pada Siswa Kelas IX.2 SMP Negeri 06 Siak Hulu - ., Ralda Gusnita Darman; ., Romi Cendra (CV. ITTC INDONESIA, 2022)
This research is a classroom action research conducted at SMP Negeri 06 Siak Hulu. This research was conducted with the aim of looking at the learning outcomes of Passing Down in volleyball games after using the Teams Games Tournament cooperative method. The sample in this study was 30 students consisting of 16 male students and 14 female students. The results of this study indicate that there is an increase in lower passing ability in volleyball games using the Teams Games Tournament Type Cooperative learning method in class IX.2 students of SMP Negeri 06 Siak Hulu. This condition can be seen in cycle I and cycle II. Where in the first cycle there were 19 students who achieved the KKM score with a percentage of 63%. Furthermore, the number of students who scored above the KKM increased in cycle II, namely to 27 students with a percentage of 90%.